Impact of SARS-CoV-2 Pandemic and Strategies for Resumption of Activities During the Second Wave of the Pandemic: A Report From Eight Paediatric Hospitals From the ECHO Network - Indolfi, Giuseppe; Stivala, Micol; Lenge, Matteo; Diaz Naderi, Ruben; McIntosh, Jennifer; Llandrich, Ricard Casadevall; Gannon, Joe; McGreevy, Kathleen S.; Trapani, Sandra; Miettinen, Päivi; Lahdenne, Pekka; Desborough, Louisa; et al. (Frontiers in Public Health, 2021)
The Severe Acute Respiratory Syndrome CoronaVirus type 2 (SARS-CoV-2) pandemic impacted the organization of paediatric hospitals. This study aimed to evaluate the preparedness for the pandemic among a European network of children’s hospitals and to explore the strategies to restart health care services. A cross‐sectional, web‐based survey was distributed in May 2020 to the 13 children’s tertiary care hospitals belonging to the European Children’s Hospitals Organization. Responses were obtained from eight hospitals (62%). Significant reductions were observed in accesses to the emergency departments (41·7%), outpatient visits (35·7%), intensive and non-intensive care unit inpatient admissions (16·4% and 13%, respectively) between February 1 and April 30, 2020, as compared with the same period of 2019. Overall, 93 children with SARS CoV-2 infection were admitted to inpatient wards. All the hospitals created SARS-CoV-2 infection preparedness plans for the diagnosis and management of infected patients. Routine activities were re-scheduled. Four hospitals shared their own staff with adult units, two designated bed spaces for adults and only one admitted adults to inpatient wards. The three main components for the resumption of clinical activities were testing, source control, and reorganization of spaces and flows. Telemedicine and telehealth services were used before the SARS-CoV-2 pandemic by three hospitals and by all the hospitals during it. Conclusion: the present study provides a perspective on preparedness for the SARS-CoV-2 pandemic among eight large European children’s hospitals, on the impact of the pandemic on the hospital activities, and on the strategies adopted to restart clinical activities.